PENGARUH EARNING PER SHARE DAN BOOK VALUE TERHADAP STOCK RETURN - Nuuridha Matiin (Politeknik Negeri Samarinda, 2020)
This study to analyze the fundamental factors that influence the company's stock returns, earnings per share (EPS), return on assets (ROA) and stock returns on four samples of computer service sub-sector companies and other devices listed on the Indonesia Stock Exchange in 2013 - 2017, which produced twenty observations. The analysis technique used in this study is to use multiple linear regression models, which are then used to analyze data and test research hypotheses. The research hypothesis was analyzed using simultaneous test and partial test with a significance level of five percent. The results of this study indicate that simultaneous earnings per share and return on assets have a significant effect on stock returns. Partially return on assets has a negative and significant effect on stock returns, while earnings per share has a positive and insignificant effect on stock returns in computer service and other equipment sub-sector companies listed on the Indonesia Stock Exchange. Kata Kunci: Earning per share, return on assets, stock return